Problem of gender culture in contemporary academic discourse - Natalia Tokova; Yuliia Maslova; Walery Zukow (Kazimierz Wielki University, 2018)
In article the issues of gender culture in contemporary academic discourse, the notion "gender culture", its constituents and types.